IMPLEMENTASI PERATURAN PRESIDEN NOMOR 125 TAHUN 2016 TENTANG PENANGANAN PENGUNGSI DARI LUAR NEGERI DI PROVINSI KEPULAUAN RIAU - utami, penny naluria (Jurnal Legislasi Indonesia, 2019)
As a result of war and bloody conflict, forcing a number of people to seek refuge in various countries, one of which is Indonesia. Indonesia arrives Rohingya refugees who were stranded in the waters of Aceh as many as 1,300 people in May 2015. Refugees who enter the territory of Indonesia are likely to cause problems so that rules are needed to deal with it. At present, there has been a Presidential Regulation Number 125 of 2016 concerning Handling of Refugees from Abroad (Perpres 125/2016). This regulation, among others, regulates the security of asylum seekers and refugees, coordinates the government and UNHCR regarding their status, and respects the fundamental freedoms of refugees. This study aims to identify the problems faced in the implementation of Presidential Regulation 125/2016 and offer a number of alternative solutions to the problems faced by the research method using a qualitative approach. The results showed that even though Indonesia was not a party to the 1951 Refugee Convention and Protocol concerning the Status of UN Refugees in 1967, Indonesia highly respected and respected the contents of the convention so that the issuance of Presidential Regulation 125/2016. However, in its implementation there are still a number of challenges and obstacles found including: lack of socialization to the Regional Government regarding the Perpres so that there are still regional heads rejecting the arrival of refugees; there is no task force for handling refugees from abroad; limited human resources and budget; unavailability of shelter land for refugees; and cause social jealousy for refugees who receive free humanitarian assistance while local residents live in shortages. Recommendations addressed to the Government of the Riau Islands Province to budget for handling refugees in the APBD; form a task force to handle refugees from abroad to optimize coordination; and the synergy of regional stakeholders.